Endometrioid like yolk sac tumor of the testis with small teratomatous foci: A case report and review of the literature - Prabir Hazarika (Wolters Kluwer Medknow Publications, 2015)
I have reported a case of endometrioid like yolk sac tumor of the testis in a 20-year-old boy. Endometrioid like yolk sac tumor is a rare tumor. A few cases have been reported in ovary. In case of male, a case of pure glandular endometrioid like yolk sac tumor is reported in a 43 years male in right undescended testis and another case of abdominal metastasis showing endometrioid pattern from mixed testicular germ cell tumor comprising of teratoma and embryonal carcinoma. My patient was a 20-year-old male presented with painless enlargement of right testis. Grossly the tumor was glistening creamish white with a multicystic appearance. Histopathological examination showed the tumor to be composed of glandular elements resembling early secretory endometrium, foci of keratinized thin squamous epithelium and a single focus of benign cartilage. The glandular elements show immunohistochemical positivity for AFP, cytokeratin 7 (CK7) and epithelial membrane antigen (EMA).